Verb movement in Biblical Aramaic: Verb-Object (V-O) and Object- Verb (O-V) relations (Acta Academica, 2001)
From text: In addition to V-S and S-V word order, O-V and V-O word order also occur in BA. In this chapter the grammatical relation between V and O is scrutinised and it will be shown how V movement in BA can serve to explain the V-O and O-V word order (in sentences lacking overt S’s).